유 · 성목 및 유 · 무핵 ‘샤인머스캣’ 포도 액아의 괴사 및 화원기 발생 특성 - 박준영(Jun Young Park); 김보민(Bo Min Kim); 정명희(Myung Hee Jung); 박희승(Hee-Seung Park) (Weon'ye gwahag gi'sulji, 2022)
본 연구는 ‘샤인머스캣’ 포도에서 발생되는 빈가지 현상의 발생원인을 구명하고자 액아의 발달과 여러 괴사 유형 및 화원기의 발생을 조사하여 액아의 특성을 파악하였다. 화원기형성률은 유목은 9월 성목은 10월에 가장 높았으나 이듬해 3월의 화원기형성률은 오히려 낮았으며, 이듬해 개화기의 화수발생률은 모든 조사기간의 화원기형성률과 비교하여 높았다. 화원기형성률에 비하여 화수의 발생이 많은 것은 환경휴면 기간에 계속적으로 부아에서 화원기가 형성되었기 때문으로 생각되나, 그럼에도 불구하고 유목과 성목 모두 빈가지가 많이 발생하였다. 마디별 위치에 따른 액아의 특성은 1번액아에서 주아 및 부아괴사율이 높고 화원기형성률이 떨어지기 때문에 비교적 괴사율이 낮고 화원기형성률이 높게 조사된 5번 전후의 마디까지 남기는 중초전정 이상의 전정으로 포도를 재배하는 것이 수량 확보에 유리할 것으로 판단되었다. 월별 비교를 통해서 성목은 휴면기간동안 유목과 GA 처리에 비해 주아괴사율이 증가하고 화원기형성률이 감소하는 것으로 조사되었다. 가지의 수세에 따른 액아의 발달은 유목과 성목 모두 가지의 길이에 따른 액아의 특성은 크게 차이가 없으나 GA 처리시에는 화원기형성률을 높이기 위해 가지길이를 최소한 80cm 이상으로 유지시켜 주어야 할 것으로 판단되었다. 또한 가지의 굵기가 너무 굵거나 얇으면 괴사율과 화원기 형성 측면에서 부정적인 영향을 미치기 때문에 3–4번 마디사이의 굵기가 유목은 8.5mm 이상 11.5mm 미만 정도가유지되도록 하며 성목은 10.0mm 이상 11.5mm 미만 정도로 유지될 수 있도록 하는 것이 유리할 것으로 판단되었다. 반면에GA 처리구의 경우 가지의 길이가 길어질수록, 굵기가 굵어질수록 화원기형성에 유리한 것으로 조사되었다. This study aimed to investigate why empty branches occur in ‘Shine Muscat’ grapevines. Moreover, it also aimed to understand the bud characteristics of grapevines by examining bud development, the occurrence of various necrosis types and inflorescence primordium formation. The rate of inflorescence primordium formation was highest in September for young vines and in October for adult vines. In contrast, the rate was rather low in March of the following year. The rate of blooming during the flowering period of the following year was higher than the rate of inflorescence primordium formation during all investigation periods. This is likely because inflorescence primordia are continuously formed in accessory buds during environmental dormancy. However, several empty branches were found in both young and adult vines. According to the location of node, the necrosis rates of primary and accessory buds were high, and the rate of inflorescence primordium formation was low in the 1st node. Therefore, higher than medium pruning could increase grape yields. Leaves should be pruned up to the nodes before and after the 5th node, which has a relatively low rate of necrosis and a high rate of inflorescence primordium formation. Monthly comparisons showed that the rate of primary bud necrosis increased during the dormancy period, and the inflorescence primordium formation rate was lower in adult vines compared to in young and gibberellic acid (GA)-treated vines. There were no significant differences in bud characteristics among the branch lengths in both young and adult vines. However, it was determined that the branch length in GA-treated vines should be at least 80 cm in order to increase the rate of inflorescence primordium formation. In addition, if the thickness of the branch is either too thick or thin, it negatively affects the rates of necrosis and the formation of the inflorescence primordium. Therefore, it is advantageous to maintain the thickness of branches between the 3rd and 4th nodes to 8.5–11.5 mm for young vines and 10.0–11.5 mm for adult vines. Furthermore, longer and thicker branches in GA-treated vines were found to be more advantageous for the formation of inflorescence primordium. KCI Citation Count: 1